Stepmother Russia, Foster Mother America : identity transitions in the New Odessa Jewish Commune, Odessa, Oregon, New York, 1881-1891 - Friedgut, Theodore H. (Borderlines (Boston, Mass.), 2014)
In the late nineteenth century, a group of radical Jewish youths from Odessa attempted to create an agricultural commune on the Oregon frontier, and in so doing developed from assimilated revolutionaries to American Jews. Theodore Friedgut relates the story of these youths and their creation, with special notice paid to the human encounters within the commune, the members' encounters with America in acquiring land and equipment-and, importantly, their encounters with their neighbors, themselves immigrant farmers on the American frontier. Among the volume's central sources is the memoir of Israel Mandelkern, which is here published for the first time. This study addresses hitherto neglected aspects of Jewish life in Russia and of the life of one of the more than a hundred Jewish agricultural colonies, and helps us understand the factors that influenced the young colony members in their transition toward becoming Americans. This is a microcosm of the experience of multitudes of immigrants.